Toward an Explanation of the Genesis of Ketamine-Induced Perceptual Distortions and Hallucinatory States - Pereira Jr., Alfredo [UNESP]; Johnson, Gene (Springer Nature, 2003)
The NMDA receptor (NMDAR) channel has been proposed to function as a coincidence-detection mechanism for afferent and reentrant signals, supporting conscious perception, learning, and memory formation. In this paper we discuss the genesis of distorted perceptual states induced by subanesthetic doses of ketamine, a well-known NMDA antagonist. NMDAR blockage has been suggested to perturb perceptual processing in sensory cortex, and also to decrease GABAergic inhibition in limbic areas (leading to an increase in dopamine excitability). We propose that perceptual distortions and hallucinations induced by ketamine blocking of NMDARs are generated by alternative signaling pathways, which include increase of excitability in frontal areas, and glutamate binding to AMPA in sensory cortex prompting Ca++ entry through voltage-dependent calcium channels (VDCCs). This mechanism supports the thesis that glutamate binding to AMPA and NMDARs at sensory cortex mediates most normal perception, while binding to AMPA and activating VDCCs mediates some types of altered perceptual states. We suggest that Ca++ metabolic activity in neurons at associative and sensory cortices is an important factor in the generation of both kinds of perceptual consciousness.
Keywords: Consciousness; Hallucination; Ketamine; NMDA receptor; Perception; acetylcholine; alpha amino 3 hydroxy 5 methyl 4 isoxazolepropionic acid; AMPA receptor; arachidonic acid; argipressin; calcium channel; calcium ion; calmodulin; carrier protein; clozapine; diazepam; dizocilpine; dopamine; G protein coupled receptor; gabapentin; glucose; glutamate receptor; glutamic acid; insulin; ionotropic receptor; kainic acid receptor; ketamine; lamotrigine; metabotropic receptor; n methyl dextro aspartic acid receptor; n methyl dextro aspartic acid receptor blocking agent; nimodipine; nitric oxide; noradrenalin; serotonin receptor; unindexed drug; association cortex; calcium transport; central nervous system; cingulate gyrus; cognitive defect; coma; consciousness disorder; dose response; euphoria; glucose metabolism; hallucination; human; learning; limbic cortex; memory; nonhuman; nucleus accumbens; perception disorder; priority journal; review; sensory cortex; solitary tract nucleus